Perancangan Sistem Absensi Berbasis Website Pada Pegawai Dan Dosen Fakultas Sains Dan Teknologi Universitas Qamarul Huda Badaruddin Bagu (UNIQHBA) - Ida Fitriyah; herliana rosika; Fahmi Syuhada (LPPM Universitas Qamarul Huda Badaruddin, 2023)
Abstract: A good academic information system is needed to support academic activities in an agency so that it is expected to facilitate the work of employees to find information and process data. One of the important things in an agency is employee attendance activities. At Qamarul Huda Badaruddhin University, employees perform attendance by using fingerprint and face recognize tools as evidence of attendance which is located in the health faculty building, or adjacent to the science and technology faculty building. However, the faculty of science and technology itself does not yet have an attendance system, to help employees and lecturers at the faculty of science and technology perform attendance easily, a special attendance system is needed at the faculty so as to make it easier for employees and lecturers at the faculty of science and technology to attend attendance without the need for a building. faculty of health and manage attendance data based on the time and date entered so that attendance data can be recapitulated easily and quickly for academic data purposes. attendance data. The coding of the system is done using Javascript, PHP, and MYSQL. The result of this research is the design of a website-based attendance system for employees and lecturers to attend attendance at the Faculty of Science and Technology, Qamarul Huda Badaruddin Bagu University Abstrak: Sistem informasi akademik yang baik sangat dibutuhkan untuk mendukung kegiatan akademik pada suatu instansi sehingga diharapkan dapat mempermudah pekerjaan pegawai untuk mencari informasi dan mengolah data. Salah satu yang penting pada suatu instansi adalah kegiatan absensi pegawai. Pada Universitas Qamarul Huda Badaruddhin, pegawai melakukan absensi dengan menggunakan alat fingerprint dan face recognize sebagai tanda bukti kehadiran yang letaknya di gedung fakultas kesehatan,atau yang bersebelahan dengan gedung fakultas sains dan teknologi. Namun, pada fakultas sains dan teknologi sendiri belum mempunyai sistem absensi, untuk membantu pegawai dan dosen pada fakultas sains dan teknologi melakukan absensi dengan mudah, maka diperlukan sistem absensi khusus pada fakultas sehingga mempermudah pegawai dan dosen pada fakultas sains dan teknologi melakukan absensi tanpa perlu kegedung fakultas kesehatan dan mengelola data absensi berdasarkan waktu dan tanggal yang diinputkan sehingga data absensi ini dapat direkap dengan mudah dan cepat untuk keperluan data akademik.Sistem absensi berbasis website ini dirancang berdasarkan (Unived Modelling Language) UML dan menggunakan fitur kamera untuk melakukan absensi sehingga mencegah manipulasi data absensi. Pengkodean sistem dilakukan dengan menggunakan Javascript, PHP, dan MYSQL.Hasil dari penelitian ini adalah rancang bangun sistem absensi berbasis website untuk pegawai dan dosen melakukan absensi pada Fakultas Sains dan Teknologi Universitas Qamarul Huda Badaruddin Bagu.